Hubungan Tingkat Stres dengan Siklus Menstruasi pada Remaja Putri di SMP Negeri 2 Gamping - Iin Oktaviani; Alfie Ardiana Sari (Jurnal Kebidanan Harapan Ibu Pekalongan, 2025)
Adolescence is a transitional phase that is prone to stress due to physical, psychological, and social changes. Excessive stress can disrupt the balance of reproductive hormones, thus triggering irregular menstrual cycles. In Indonesia, 13.7% of women aged 10-59 years experience irregular menstrual cycles, and in D.I Yogyakarta it reaches 15.8%. The purpose of this study was to determine the relationship between stress levels and menstrual cycles in female adolescents at SMP Negeri 2 Gamping. This research method uses a quantitative approach with a cross-sectional design. The population of this study was 60 female students of SMPN 2 Gamping with a sample size of 52 female students selected using the proportionate stratified random sampling technique. Data collection was carried out using the Perceived Stress Scale (PSS-10) questionnaire to assess stress levels and questionnaires regarding the menstrual cycle. Data were analyzed univariately and bivariately using the Chi-Square test. The results showed that most respondents with moderate stress were 20 people (38.5%) and experienced irregular menstrual cycles. The results of statistical tests show a significant relationship between stress levels and menstrual cycles p = (0.001). It is concluded that there is a relationship between stress levels and menstrual cycles in female adolescents at SMP Negeri 2 Gamping.